Recombinant Porcine 12-Lipoxygenase Catalytic Domain: Effect of Inhibitors, Selectivity of Substrates and Specificity of Oxidation Products of Linoleic Acid - Jiamei Xu; Yu Liu; Jingjing Ma; Pengpeng Li; Zhiming Geng; Daoying Wang; Muhan Zhang; Weimin Xu (Foods, 2022)
Lipoxygenase (LOX) is a major endogenous enzyme for the enzymatic oxidation of lipids during meat storage and meat product manufacturing. In the present work, some characteristics, i.e., effects of inhibitors, selectivity of substrates and specificity of oxidation products, were studied using recombinant porcine 12-lipoxygenase catalytic domain (12-LOXcd). Several familiar inhibitors were found inhibit the activity of recombinant porcine 12-LOXcd;nordihydroguaiaretic acid demonstrated the strongest inhibitory effect. The enzyme could oxygenate common polyunsaturated fatty acids, and showed the highest affinity to linoleic acid (LA), followed by arachidonic acid (AA), linolenic acid (LN) and docosahexaenoic acid (DHA). Under the action of porcine 12-LOXcd, LA was oxidized into four hydroxyoctadecadienoic acid (HODE) isomers, i.e., 13-Z,E-HODE, 13-E,E-HODE, 9-Z,E-HODE and 9-E,E-HODE. Variation of pH not only affected the yield of LA oxidation products, but also the distribution of HODE isomers. These results indicated that endogenous LOX activity and LOX-catalyzed lipid oxidation can be regulated during meat storage and meat product manufacturing.